Microdevice‐based solid‐phase polymerase chain reaction for rapid detection of pathogenic microorganisms - Pham, Quang Nghia (Biotechnol Bioeng, 2018)
We demonstrate the integration of DNA amplification and detection functionalities developed on a lab‐on‐a‐chip microdevice utilizing solid‐phase polymerase chain reaction (SP‐PCR) for point‐of‐need (PON) DNA analyses. First, the polycarbonate microdevice was fabricated by thermal bonding  to contain microchambers as reservoirs for performing SP‐PCR. Next, the microchambers were subsequently modified with polyethyleneimine and glutaraldehyde for immobilizing amine‐modified forward primers. During SP‐PCR, the immobilized forward primers and freely diffusing fluorescence‐labeled reverse primers cooperated to generate target amplicons, which remained covalently attached to the microchambers for the fluorescence detection. The SP‐PCR microdevice was used for the direct identifications of two widely detected foodborne pathogens, namely Salmonella spp. and Staphylococcus aureus, and an alga causing harmful algal blooms annually in South Korea, Cochlodinium polykrikoides. The SP‐PCR microdevice would be versatilely applied in PON testing as a universal platform for the fast identification of foodborne pathogens and environmentally threatening biogenic targets.